2017
DOI: 10.1093/cz/zox064
|View full text |Cite|
|
Sign up to set email alerts
|

Exposure to cuticular bacteria can alter host behavior in a funnel-weaving spider

Abstract: Contact with environmental microbes are arguably the most common species interaction in which any animal participates. Studies have noted diverse relationships between hosts and resident microbes, which can have strong consequences for host development, physiology, and behavior. Many of these studies focus specifically on pathogens or beneficial microbes, while the benign microbes, of which the majority of bacteria could be described, are often ignored. Here, we explore the nature of the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…We found no effect of exposing males to bacteria on their courtship behaviour (as has been found in other host–parasite systems: Abbot & Dill, ; McLachlan, ), perhaps because this was a topical application while female exposure was an internal application. Although similar topical applications of cuticular bacteria have been found to influence spider behaviour (Keiser, Shearer, et al, ; Keiser, Wright, et al, ; Parks et al, ), more detailed experiments are needed to illuminate the mechanistic underpinnings shaping the relationship between bacterial exposure and sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found no effect of exposing males to bacteria on their courtship behaviour (as has been found in other host–parasite systems: Abbot & Dill, ; McLachlan, ), perhaps because this was a topical application while female exposure was an internal application. Although similar topical applications of cuticular bacteria have been found to influence spider behaviour (Keiser, Shearer, et al, ; Keiser, Wright, et al, ; Parks et al, ), more detailed experiments are needed to illuminate the mechanistic underpinnings shaping the relationship between bacterial exposure and sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…However, we took precautions to adhere to the ASAB/ARRIVE Guidelines for the Use of Animals in Research to minimize unnecessary stresses or harm to the spiders. A recent study showed that a similar application of cuticular bacteria to A. pennsylvanica was not detrimental to survival (Parks et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some cuticular bacteria induce weight loss, mortality, and changes to host behavior when re-applied in large quantities, as has been shown in the grass spider Agelenopsis pennsylvanica (CL Koch, 1843) (Parks et al 2018) and the social spider Stegodyphus dumicola Pocock, 1898 (Keiser et al 2016b). It is unlikely that exposure to cuticular bacteria alone can induce these changes, but none of these studies identified the route by which bacteria enter the host body after a topical application.…”
Section: Major Groups That Parasitize Spidersmentioning
confidence: 99%